Effective and new technologies in kidney tissue engineering - Rayat Pisheh, Hossein; Haghdel, Mobin; Jahangir, Mahboube; Hoseinian, Monireh Sadat; Rostami Yasuj, Shaghayegh; Sarhadi Roodbari, Ali (Frontiers in Bioengineering and Biotechnology, 2024)
Kidney disease encompasses a wide spectrum of conditions, ranging from simple infections to chronic kidney disease. When the kidneys are unable to filter blood and remove waste products, these abnormalities can lead to kidney failure. In severe cases of kidney failure, kidney transplantation is considered the only definitive treatment. Worldwide, the World Health Organization (WHO) repeatedly emphasizes the importance of organ donation and increasing transplantation rates. Many countries implement national programs to promote the culture of organ donation and improve patient access to kidney transplantation. The extent to which this procedure is performed varies across countries and is influenced by several factors, including the volume of organ donation, medical infrastructure, access to technology and health policies. However, a kidney transplant comes with challenges and problems that impact its success. Kidney tissue engineering is a new approach that shows promise for repairing and replacing damaged kidney tissue. This article reviews recent advances in kidney tissue engineering, focusing on engineered structures such as hydrogels, electrospinning, 3D bioprinting, and microfluidic systems. By mimicking the extracellular environment of the kidney, these structures provide suitable conditions for the growth and development of kidney cells. The role of these structures in the formation of blood vessels, the mimicry of kidney functions and the challenges in this field were also discussed. The results of this study show that kidney tissue engineering has high potential for treating kidney diseases and reducing the need for kidney transplantation. However, to achieve clinical application of this technology, further research is required to improve the biocompatibility, vascularization and long-term performance of engineered tissues.